Alternative conceptions concerning interference and diffraction of light - Coetzee, Annaretha (My University, 1998)
The aim of this study was to determine whether alternative conceptions about interference and diffraction do indeed exist, to identify the most important of these conceptions and to determine whether these conceptions relate to textbooks, as one of the main sources of students' knowledge. An analysis of secondary level textbooks and tertiary level non-calculus textbooks revealed that presentations of constructive and destructive interference, diffraction and other related aspects are treated inconsistently and in some cases contradictorily by different authors. The research instrument was a Physical Optics test which Physics students of the Technikon Pretoria wrote. This test revealed that alternative conceptions on elementary principles of interference and diffraction of light do exist and that they relate to textbook presentations. This study reveals that (i) the terms in phese and out of phase are not consistently used in different textbooks; (ii) the definitions of constructive and destructive interference in terms of phases cause major aiternative conceptions, (iii) the interrelation between interference and diffraction is not clarified.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Science in Education at the Faculty of Science, University of the Witwatersrand, Johannesburg.
Keywords: Optics--Study and teaching (Secondary)--South Africa; Optics--Study and teaching (Higher)--South Africa; Textbooks; Diffraction--Study and teaching (Secondary)--South Africa; Diffraction--Study and teaching (Higher)--South Africa; Interference (Light)--Study and teaching (Secondary)--South Africa; Interference (Light)--Study and teaching (Higher)--South Africa